Religion and language as the main categories in the structure of social consciousness (Eurasian Journal of Religious Studies, 2025)
This study aims to delve deeper into the role of religion and language in shaping public consciousness and to analyze the interrelation between them. The main objective of the study is to identify the mechanisms by which religion and language influence public consciousness and to analyze the social, cultural, and historical aspects of this process. The study provides definitions of the concepts of "religion" and "language" and describes the structure and functions of public consciousness. Furthermore, a comparative analysis of the role of religion and language in shaping public consciousness in different historical periods and cultures is conducted. The research results are of theoretical significance for such scientific disciplines as religious studies, sociology, psychology, and linguistics. In addition, the results of this study can be useful in shaping government policy, as well as in improving mutual understanding between different ethnic groups. The study used methods such as systematic literature review, comparative analysis, and observation. The study found that religion and language are among the main factors shaping public consciousness. Moreover, it was proven that religion and language are important factors determining the direction of social change. This study allows for a deeper understanding of the mechanisms of influence of religion and language on public consciousness and makes a new contribution to the local researches in this field. The research results can be applied in various fields, including education, culture, politics, and religious relations.Keywords: Religion, Language, Public Consciousness, Religious Consciousness, Culture